2014
DOI: 10.5433/1679-0359.2014v35n4p2185
|View full text |Cite
|
Sign up to set email alerts
|

Silagem de aveia branca em função da adubação nitrogenada e pré-murchamento

Abstract: A conservação da forragem na forma de silagem é uma forma de fornecer volumoso de qualidade em épocas de baixa oferta de pastagem, com isso, objetivou-se avaliar o efeito do pré-murchamento e da adubação nitrogenada nos parâmetros fermentativos e valor nutritivo da silagem de aveia branca, em dois estádios de colheita. O experimento foi conduzido em 2011, na UTFPR, Dois Vizinhos-PR, em delineamento de blocos ao acaso com esquema bifatorial com três repetições. Os tratamentos principais foram seis doses de nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Thus, it may consist of a positive point for silages dehydrated by the chemical method. an improved fermentation of ensiled mass (ZAMARCHI et al, 2014). David et al (2010) reported pH of 4.7 in oat silage cut at the early flowering stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it may consist of a positive point for silages dehydrated by the chemical method. an improved fermentation of ensiled mass (ZAMARCHI et al, 2014). David et al (2010) reported pH of 4.7 in oat silage cut at the early flowering stage.…”
Section: Resultsmentioning
confidence: 99%
“…Zamarchi et al (2014), in an experiment with oat, ensiled fodder after 6 hours of dehydration and obtained NDF values of 66.69% and ADF of 38.36. Yet, Paris et al (2015), in an experiment with oat silage cut in the early flowering and dehydrated by a mechanical method, obtained NDF of 55.8% and ADF of 37.21%, which are values lower than were the ones we found in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the use of pre-dried silage of temperate forages is still considered as an alternative to providing quality forage in periods of pasture shortage (Zamarchi, Pavinato, Menezes, & Martin, 2014). However, in Europe, the winter cereals have shifted from the status of strategic forage crops during food shortage periods to a status of basal forage crop of diets, constituting a real strategy in forage planning (Debaeke & Bertrand, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Silage is a product of forage conservation through anaerobiosis, in which soluble carbohydrates are converted into organic acids by acid-lactic bacteria, preserving the nutritional value (Zamarchi et al, 2014). Ensilage of grasses is an alternative to supply quality silage in period of pasture scarcity (Paris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%